Maritime Archaeology and Maritime Heritage Protection in the Disputed Territory of Northern Cyprus - Harpster, Matthew (Springer, 2008)
Between 1967 and 1974, the island of Cyprus was a centre of maritime archaeology in the eastern Mediterranean. Individuals such as Michael and Susan Katzev, George Bass, Jeremy Green and Richard Steffy were living on and visiting the island, and testing and developing methods still common in the discipline. The hostilities on Cyprus in the summer of 1974 and the implementation of international regulations limiting archaeological work in the northern portion of the island, however, had repercussions still evident today. This article summarizes past maritime archaeological work along the northern coastline, addresses the regulations limiting archaeological activity in the region and discusses a new training program licensed by the Nautical Archaeology Society aiding in the protection of the island's maritime heritage representing approximately 10,000 years of activity.
Keywords: Maritime heritage; Cyprus; UNESCO; Protection of cultural heritage; History of maritime archaeology